Heaven on Earth reimagining time and eternity in nineteenth-century British evangelicalism - Spence, Martin (Eugene, Oregon Pickwick Publications, 2015)
"In nineteenth-century Britain, a large number of prominent Anglican and Presbyterian Evangelicals rejected the idea that salvation meant "going to heaven when you die." Instead, they proposed that God would establish his kingdom on earth, renewing the creation and reanimating embodied humans to live in a world of science and progress. This book introduces the writings and activities of these women and men, among whom were counted the ardent social reformer Lord Shaftesbury, the highly-respected clergyman Edward Bickersteth, the popular author Charlotte Elizabeth Tonna, and the General Secretary of the Evangelical Alliance, Thomas Rawson Birks. The book shows that the catalyst for such theological revisionism was the end-times doctrine known as "premillennialism." While commonly characterized as a gloomy and sectarian belief, the book argues that premillennialism in Victorian Britain was actually an optimistic and often liberalizing creed. It dissolved older Evangelical assumptions about the dissimilarities between time and eternity, body and soul, heaven and earth. The book demonstrates that, far from being eccentric pessimists, premillennialists were actually pioneers of trends in nineteenth-century Christian theology that stressed the importance of the incarnation, prioritized social justice, and even entertained the idea of universal salvation"--Page 4 of cover
Literaturverzeichnis: Seite 269 - 298
Keywords: Eschatology -- History of doctrines -- 19th century; Millennium (Eschatology) -- History of doctrines -- 19th century; Evangelicalism -- Great Britain -- History -- 19th century